Power, Resistance, and Religious Values: an Anthropological Study in The Film “Tuhan, Izinkan Aku Berdosa” - Nururi , Imam; Yudianto, Asep; Abduh, Muhammad; Kurniawan, Fahmi (Ath Thariq Jurnal Dakwah dan Komunikasi, 2025)
The film “Tuhan, Ijinkan Aku Berdosa” represents the relationship of power and resistance in the social and religious context of Indonesian society. This study aims to analyze how power is interpreted, exercised, and resisted in the film’s narrative, and how this representation is related to the function of film as a medium of da’wah that conveys moral and religious values. This study uses a qualitative approach with text analysis design, symbolic representation analysis techniques, and Michel Foucault’s theory of power. An anthropological perspective is applied by reading the film as a cultural artifact that reflects the social dynamics of society, especially in terms of views on sin, repentance, and moral authority. The results of the analysis show that power in the film appears as a mechanism of oppressive social control as well as a trigger for spiritual transformation. Religious values ​​and repentance rituals function as forms of symbolic resistance and become part of a da’wah strategy that is relevant to the modern social context. This study contributes to the study of film as a space for the representation of power as well as a medium for communicative and transformative da’wah.